100 Jahre Erziehungswissenschaft an der Georg-August-Universität Göttingen 1920-2020 - Bers, Christiana (Universitätsverlag Göttingen, 2020)
In 2020, the Institute for Educational Science celebrated its 100-year anniversary - in 1920 Herman Nohl became the first professor for Pedagogy and subsequently founded the Pedagogic Seminar in July 1920. In celebration of this jubilee, the contributions to this edition bring forward various aspects of the history of educational science at the University of Göttingen. The book includes two lectures, which were given during the ceremonial act on 29 January 2020 and discuss the development of pedagogy as a discipline before its institutionalization. Additionally, it sheds light onto names, places and programs, which played an important part in the Institute's history. Finally, the research methods are discussed from a reflexive point of view, including questions regarding data collection and the presentation of results.